Economic growth and (re-)distributive policies in a non-cooperative world - Günther Rehme (Technische Universität Darmstadt, Department of Law and Economics, 2006)
Many models show that redistribution is bad for growth. This paper argues that in a non-cooperative world optimizing, redistributing ('left-wing') governments mimic non-redistributing ('right-wing') policies for fear of capital loss if capital markets become highly integrated and the countries are technologically similar. 'Left-right' competition leads to more redistribution and lower GDP growth than 'left-left' competition. Efficiency differences allow for higher GDP growth and more redistribution than one's opponent. Irrespective of efficiency differences, however, 'left-wing' governments have higher GDP growth when competing with other 'left-wing' governments. The results may explain why one observes a positive correlation between redistribution and growth across countries, and why capital inflows and current account deficits may be good for relatively high growth.
Keywords: O4; H21; D33; C72; F21; 330; Growth; Distribution; Tax Competition; Capital Mobility; Wirtschaftswachstum; Verteilungspolitik; Steuerwettbewerb; Internationale Kapitalmobilität; Public Choice; Nichtkooperatives Spiel